Researches regarding increase of impact resistance for welded structures by weld micro-alloying. (January 2020) - Zgripcea, L; Heput, T; Putan, V; Ardelean, M
Abstract: In industrial fabrication, structural steel is the most used grade used in structures and automotive. For these grades, in the last decade automation and standardization leaded to increase of mechanical properties and reduction of fabrication cost. In parallel, control of alloying elements and impurities realized especially in vacuum treatment stations ensured higher mechanical properties in a larger temperature domain. The research scope is to increase of mechanical properties for weld line and obtain higher properties than the base metal. Final goal is to obtain steel structures assembled by welding safer in exploitation. Key point of the research is to increase the impact resistance for weld line by micro alloying and determine the optimum percentage for nickel element inside weld metal.